A coupled viscoplastic-damage constitutive model for semicrystalline polymers. (January 2023) - Wiersma, Jeffrey; Sain, Trisha
Abstract: In the present work, the large deformation rate-dependent constitutive behavior of isotactic polypropylene is studied via an experimentally validated macroscale constitutive model. To analyze the nonlinear rate-dependent response of the material, mechanical tests are conducted at room temperature and a phenomenological constitutive model is proposed to describe the viscoplastic yielding and damage response of the semicrystalline polymer. The constitutive model is based on a finite deformation elastic-viscoplastic framework that can predict the rate dependent response of semicrystalline polymers under tension and compression. In addition, a continuum scale damage model coupled with viscoplasticity is adopted to incorporate cavitation induced damage growth, coalescence, and fibrillation in the material. To validate the proposed model, uniaxial compression and tension experiments are conducted on isotactic polypropylene homopolymer within strain rates of 10–3 s-1 to 10-1 s-1. The constitutive model is implemented in a finite element program ABAQUS/Explicit (ABAQUS, 2017) by writing a user material subroutine (VUMAT). With the model parameters properly calibrated, the present study shows that the proposed constitutive model is able to predict the macroscopic rate dependent load-displacement curves, as well as the fracture responses for various standard geometries. Highlights: A coupled viscoplastic damage model is proposed for semicrystalline thermoplastic polypropylene. model is based on a homogenized microstructural assumption of a semi crystalline polymers. a large deformation elasto-viscoplastic constitutive framework combined with a continuum level damage model . Experiments have been conducted and the model predictions are validated.